A Cross-sectional Observational Study of Adverse Drug Reactions among Patients in Nephrology Department at a Tertiary Care Teaching Hospital - Prasad, P. Dharani (Asian Journal of Pharmaceutics (AJP), 2024)
Background: The World Health Organization defines adverse drug reaction (ADR) as “A response to a drug, that is noxious and unintended, occurs at doses normally used in humans for the propylaxis, diagnosis, and treatment of disease, for the modifications of physiological function.” Clinical pharmacists play an important role in ADR monitoring and reporting, as the majority of serious ADR’s occur in a hospital setting and contribute to a significant proportion of hospital admissions. Early detection of the ADR’s helps in minimizing and preventing the ADR’s by modifying the dose or changing the offending agent. Aim: Pharmacovigilance studies are essential in Nephrology and its main aim is to reduce the risk of drug related problems in patients. Materials and Methods: This study was Hospital based cross-sectional observational study conducted in Department of Nephrology, Sri Venkateswara Institute of Medical Sciences, South Indian a tertiary care hospital, Tirupati, Andhra Pradesh. This study was approved by the Institutional Research and the Ethics Committee of the hospital. This study used a minimum sample size of 113 participants. Results: Out of 113 patients who were treated in nephrology department, 58 (51.32%) patients developed ADRs. Of the 58 patients, 36 (62.06%) are men and 22 (37.93%) are women. Patients of 39–48 (29.31%) age group are mostly affected. Among 58 patients, the causality assessment of 18 patients (31.03) was found to be Possible and the remaining 40 patients (68.96) was found to be Probable. The commonly developed ADRs include “pedal edema, hypokalemia, and maculopapular rash.” Discussion: ADRs mimic many diseases and result in severe morbidity and mortality, making them a major clinical concern. Adverse medication events are undoubtedly more frequent in hospitalized patients with chronic kidney disease and other comorbidities. Conclusion: The present study has generated a useful baseline data regarding ADRs in various categories such as age- and gender-wise distribution of ADRs. By educating the patients about the ADRs, it also contributed to improve the patient’s health-related quality of life.